Sosialisasi Pemanfaatan Sampah Dan Penanaman Pohon Mangrove Desa Laulalang Kabupaten Tolitoli - Moh. Mudassir Ali; Ramdan Yusuf; Ramlah Ilham Darise (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2023)
The importance of maintaining a clean and healthy environment is necessary to develop a character education program "Love the Environment" for the residents of Laulalang Village. This program must also teach them how to take care of nature to protect them once again from the dangers of coastal abrasion through a greening program. This community service aims to achieve a green economy in the government system of Laulalang Village which targets the village community, especially housewives, In addition to being able to help the household economy, teenagers are also aware of the environment for the future. This program was implemented in Laulalang Village, North Tolitoli District, Tolitoli. It consists of several series of activities including socialization on waste utilization, and a mangrove tree planting program. The series of activities were carried out over two days. The result of this activity is that the community can recycle or classify types of waste that can be resold so that it has new economic value, where everything can have economic value if it is managed properly and appropriately, so it does not pollute the environment which can be detrimental to all. Then the planting of mangrove trees to create new environmental ecosystem conditions to grow and develop again along the northern coastline of Laulalang Village, with the hope that it will create a new network, a future network for Sulawesi's marine ecosystems, followed by an advanced generation who are aware of the environment for the future come.